UPAYA GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2021)
School or Madrasah is an educational institution in which the learning process occurs, which involves teachers and students. In order to always be able to exist in carrying out its function as an educational institution, education implementers in schools must be aware of anything that can support or influence the teaching and learning process, so that they can understand each other, and together can formulate appropriate formulations in carrying out the teaching and learning process. Learning interest is an indicator that supports or influences a student's learning. Students who have a strong interest in a particular subject, then naturally feel very interested and happy in learning these subjects. Unlike someone or students who have no interest in a particular subject, it will be easy to feel bored and even lazy in learning the lesson. Interest is a feeling of preference or a feeling of interest in a thing and activity, without anyone asking. Therefore, the teacher must have a strategy that can arouse students' interest in their learning. As a teacher, they are required to be skilled and to master teaching materialsas well as to be creative and innovative in delivering their teaching materials. So that the implementation of the teaching and learning process can run optimally, the efforts of teachers in increasing interest in learning need to be taken seriously.